Peningkatan Pengetahuan Ibu tentang ASI Eksklusif, Gizi Anak, Gizi Keluarga, dan Personal Hygiene melalui Pendekatan Home Visit dan Media Leaflet di Desa Mata Wawatu - Ardinawati Ardinawati; Asnita Sari; Dwi Febriani; Evitri Anggraeni; Fadilla Aulia Savana; La Ode Rifaldy Rizqi Ramadan.M; Miftahul Hasanah; Mila Angraeni; Muhammad Arifin; Rifdah Molidah; Rizda Sandiva Saputri; Rossa Aprilia Wulan As’ad`; Wa Ode Yanti; Zahra Nuril Anwar; Zahratul Jannah; Devi Savitri Effendy; Ramadhan Tosepu; Nurmaladewi Nurmaladewi; Suhadi Suhadi (Lembaga Pengembangan Kinerja Dosen, 2025)
This article explores the significance of exclusive breastfeeding, child nutrition, and personal hygiene in enhancing maternal and child health. The study aimed to enhance mothers' knowledge about exclusive breastfeeding, child nutrition for ages 0-24 months, and personal hygiene through home visits and leaflet distribution. The program was conducted in 15 households in Mata Wawatu Village, utilizing Pre-Test and Post-Test assessments to evaluate knowledge changes. The findings indicated a notable improvement in mothers' understanding following the educational interventions. Additionally, the appealing leaflet media contributed to raising public awareness.